Minimally invasive coronary artery bypass grafting with ultrasonically skeletonized internal thoracic arteryCentral MessagePerspective - Kazutoshi Tachibana, MD, PhD; Keita Kikuchi, MD, PhD; Kouhei Narayama, MD; Akihito Okawa, MD; Yu Iwashiro, MD; Ayaka Arihara, MD; Akihiko Yamauchi, MD, PhD (JTCVS Techniques)
Objective: This study aimed to examine the feasibility and safety of minimally invasive cardiac surgery coronary artery bypass grafting using an ultrasonically skeletonized internal thoracic artery in the authors’ initial experience. Methods: From February 2012 to May 2021, 247 consecutive patients who underwent minimally invasive coronary artery bypass grafting using an ultrasonically skeletonized internal thoracic artery were reviewed retrospectively. Internal thoracic arteries were harvested in a full skeletonized fashion using an ultrasonic scalpel via left minithoracotomy. Bilateral internal thoracic arteries were used in 108 patients, and the internal thoracic arteries as in situ grafts were used in 393 anastomoses. Total arterial revascularization was performed in 126 patients, and 142 patients underwent aortic nontouch minimally invasive coronary artery bypass grafting. Results: The patients’ mean (range) age was 65.9 ± 11.5 (30-90) years. The mean (range) number of anastomoses performed was 2.6 ± 1.1 (1-6). Forty-six patients (18.6%) had 4 grafts, 94 patients (38.1%) had 3 grafts, and 60 patients (24.3%) had 2 grafts. Minimally invasive coronary artery bypass grafting was completed without conversion to sternotomy in all patients. Cardiopulmonary bypass was performed in 3 patients (1.2%), reinterventions due to bleeding were performed in 7 patients (2.8%), and chest wound infections were observed in 5 patients (2.0%). There was 1 (0.4%) mortality. Conclusions: Minimally invasive coronary artery bypass grafting using an ultrasonically skeletonized internal thoracic artery is feasible and has shown good perioperative outcomes. This approach has the potential for further optimization with revascularization strategies.